Efficacy of a Model Nano-TiO2 Sunscreen Preparation as a Function of Ingredients Concentration and Ultrasonication Treatment - Simzar Hosseinzadeh, Hadi Baharifar, Amir Amani (Tabriz University of Medical Sciences, 2017)
Background: TiO2 nanoparticles (NPs) which are used in sunscreen formulations are able to block ultraviolet (UV) radiation with a higher efficiency compared with micro-scale particles. The concentration of corresponding particles is an important factor in UV attenuation effects as well as cell toxicity profiles. Herein, TiO2 NPs were dispersed using ultrasonication treatment and a sunscreen cream was prepared using TiO2 NPs. Methods: The effect of TiO2 concentration (i.e. a physical barrier) and octocrylene (i.e. a chemical UV filter) as well as sonication time (i.e. aggregation preventer) were studied on UVB blocking efficiency of the preparation by measurement of sun protection factor (SPF). Response surface methodology was employed to investigate the effect of the inputs (independent parameters) on the output (dependent parameter). Results: Findings indicated that maximum amount of nano-TiO2 and octocrylene make the preparation most effective. The effect of ultrasonication in breaking the agglomerates was however dominated by the effect of concentration of octocrylene, possibly due to hydrophobic interactions between NPs and octocrylene. Also, TiO2 NPs showed a significant increase in cytotoxicity profile of the preparation. Conclusion: In conclusion, introduction of the nanoparticles, as the dominant factor, to the sunscreen product increased both efficacy and cytotoxicity of the product.